Biofilm Shows Independency form Hemolysin Genes Arsenal in Methicillin Resistant Staphylococcus Aureus - Jaddoa, Nihad Taha mohammed; Al-Mathkhury, Harith Jabbar Fahad (Iraqi Journal of Science, 2018)
Normally, bacteria exposed to antibiotics at sub minimal inhibitory concentrations (MIC) inside the host. Therefore, the current study aimed to comprehend the association among hemolysins, biofilm, as well as gentamicin resistance in local MRSA isolates. Around 35 Staphylococcus aureus locally isolated from different clinical specimens were employed in this study. Methicillin resistance was detected via cefoxitin disk diffusion and mecA amplification methods. MIC of gentamicin was estimated by broth microdilution method. Hemolysin genes involving hla, hlb, hld, and hlg were determined using multiplex polymerase chain reaction (PCR) technique. Microtiter plate method was employed for biofilm assessment in the presence and absence of gentamicin at sub MIC. Moreover, atomic force microscopy technique was employed for confirming the effect of gentamicin on biofilm. The present findings revealed that methicillin resistant S. aureus (MRSA) constituted, nearly, 94.29% (33 isolates) of all S. aureus isolates. Around 12 (36.36%), four (12.12%), and 17 (51.51%) isolates were gentamicin-sensitive, intermediate, and resistant to gentamicin, respectively. hla and hld were located in 32 out 33 MRSA isolates. All MRSA isolates succeeded in forming biofilm; however, three (0.09%), 23 (69.69%), and seven (21.21%) isolates formed weak,moderate, andstrong biofilm, respectively. Gentamicin at sub MIC reduced the intensity of biofilm and the AFM confirmed this finding. In conclusion, very weak correlation linked the biofilm formation capacity and isolate MIC. On the other hand, possession of hemolysin genes seems has no correlation with biofilm formation. Nevertheless, gentamicin at sub MIC reduced the intensity of MRSA biofilm.